(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the content and essence of the pedagogical foundations of developing the spiritual competence of high school students today. Many programs on improving the quality and efficiency of education, forming their practical skills in subjects, and opinions on the priority tasks were expressed.